2023
DOI: 10.1021/acsami.3c12351
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Artificial Solid–Electrolyte–Interphase Layer for Long-Life Sodium Metal Batteries

Roya Damircheli,
Binh Hoang,
Victoria Castagna Ferrari
et al.

Abstract: Sodium metal batteries have garnered significant attention due to their high theoretical specific capacity, cost effectiveness, and abundant availability. However, the propensity for dendritic sodium formation, stemming from the highly reactive nature of the sodium metal surface, poses safety concerns, and the uncontrollable formation of the solid–electrolyte interphase (SEI) leads to large cell impedance and battery failures. In this study, we present a novel approach where we have successfully developed a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…For instance, it has been reported that the SnF 2 coating layers can be converted into NaF and Na‐Sn rich protective layer on the Na metal, which could significantly enhance the cycling stability of the Na metal anodes. [ 119 ]…”
Section: Research Advances For Rt‐na/s Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it has been reported that the SnF 2 coating layers can be converted into NaF and Na‐Sn rich protective layer on the Na metal, which could significantly enhance the cycling stability of the Na metal anodes. [ 119 ]…”
Section: Research Advances For Rt‐na/s Batteriesmentioning
confidence: 99%
“…[109] A composite SEI layer with Na 2 Te, NaTe, TeO 2 , TeF 4 , Na 2 TeO 4, and other organic components could be observed, which exhibited good structural stability to enable stable cycling of the Na metal anodes in carbonate electrolyte for 700 h. A series of Na + conductive transition metals (In, Bi, Zn, Sn) have been investigated as protective coating layers for Na metal anodes, and the results demonstrated that the Na-In composite anode delivered the most stable cycling performance for 800 h at 5 mAh cm −2 with a low nucleation potential and regulated Na + flux. [108] Many transition metal compounds have also been reported as coating layers for Na metal anodes, including SnF 2 , [119] SbF 3 , [120] V 2 S 3 , [116] Mo 6 S 8 , [121] MoS 2 , [122] V 2 P, [117] BiVO 4 , [156] etc. The compounds could be converted into intermetallic alloys to regulate Na metal plating and inorganic sodium salts as components for stable SEI layers.…”
Section: Artificial Sei Layersmentioning
confidence: 99%
See 1 more Smart Citation